Association of post-stroke-initiated antidepressants with long-term outcomes in young adults with ischaemic stroke. (31st December 2022) - Broman, Jenna; Aarnio, Karoliina; But, Anna; Marinkovic, Ivan; Rodríguez-Pardo, Jorge; Kaste, Markku; Tatlisumak, Turgut; Putaala, Jukka
Abstract: Objective: We examined the association between initiation of antidepressants within the first year after ischaemic stroke (IS) in young adults and long-term fatal and non-fatal cardiovascular events, as well as all-cause mortality. Patients and methods: The Helsinki Young Stroke Registry (HYSR) includes patients aged 15–49 years with their first-ever IS occurring 1994–2007. From nationwide registers, we obtained data on prescriptions (1993–2011) and outcomes of interest (1994–2011). Time of initiating post-stroke antidepressants (PSADs) was defined as time of the first filled prescription for antidepressants within the first year from IS. To account for non-random assignment of PSADs, we performed propensity score matching and studied the relationship between PSAD initiation and outcomes using Cox regression models with time-varying coefficients. Results: Of all patients ( n  = 888), 206 (23.2%) initiated PSADs within the first year, of which 203 (98.5%) could be matched to 406 non-initiators. In this matched sample of 609 patients, the median follow-up time was 8.1 (interquartile range [IQR] 5.0–12.6) years and 169 (28.9%) patients had any cardiovascular events, 95 (15.8%) had recurrent ischaemic or haemorrhagic strokes and 106 (17.4%) died. Adjusted for sociodemographics and cardiovascular comorbidities, PSAD initiation was associated with recurrent ischaemic or haemorrhagic stroke 5–10 years after IS (hazard ratio [HR] 3.07, 95% confidence interval [CI] 1.32–7.12). No association emerged between PSAD initiation and other outcomes. Conclusions: In young adults, PSAD initiation within the first year after IS was associated with a heightened hazard of recurrent ischaemic or haemorrhagic stroke in the long term. Future studies are needed to verify the results and to further study the nature of this finding. KEY MESSAGES: Initiation of post-stroke antidepressants (PSADs) within the first year after ischaemic stroke (IS) was associated with a heightened hazard of recurrent ischaemic or haemorrhagic stroke in the long term. Patients starting antidepressants after IS should be followed up more closely in case of recurrent events. Future studies are needed to verify the results and to further study the nature of this finding.